Blood Husband: An Interpretation of Exodus 4.24-26 from the Jewish Tradition - Neto, Willibaldo Ruppenthal (Vox Scripturae - Revista Teológica Internacional, 2017)
This article aims to show some considerations about Exodus 4.24-26, interpreting it from the relationship with other Old Testament texts, and specially with texts of the rabbinic Judaism tradition. From the study of Circumcision in the Old Testament, it is exposed its  connection with Easter, explained in the account by the presence of the “angel of death” and even by blood with salvific character. Finally, will be explained the expression hatan damin, “bloody husband”, from Jewish tradition about Moses, Zipporah and even Jethro.
Keywords: Circumcision; Moses; Exodus; Old Testament